The Use of Joylada Application in Teaching Narrative Writing - Mutiarani Mutiarani; Muhamad Sofian Hadi; Elka Caesarina (Universitas Teknokrat Indonesia, 2022)
The research aimed to increase students’ writing skills on narrative text in English lesson by using Joylada application. The subject of this research was eighth-graders at one of Junior High School in South Tangerang City which considered 40 students. The method of this research was quantitative method with pre-experimental study. The data were collected by giving pre-test and post-test as the instruments. The result of this research showed that there was increasing of student in narrative writing skill. The result was calculated by using t-test. The findings proved that the students in pre-test was 2500 with the mean score 62.5. The lowest score was 48 and the highest score was 75. Meanwhile, in the result of post-test 3336 with a mean 83.4. The lowest score was 75 and the highest score was 95. From the score result, it can be concluded that the higher score was post-test. The results of the t-test calculation showed that t-cal was 17.5 and t-table with degrees of freedom (df) 40 obtained 1.68. The significance value was less than 0.05 and t-cal > t-table. The result can be concluded that the Joylada application can be unique and an alternative for teaching narrative writing skills. The students can increase their narrative writing skills through Joylada application.